THE BASIC CONCEPT OF THE MOSQUE DESIGN IN ACCORDANCE WITH THE HOLY QUR’AN AND HADITS - Edrees, Munichy Bachron (Journal of Islam and Science, 2014)
The Quba mosque which was constructed by Prophet Mohammed in 622 A.D constitute the best example of the mosque for the members of the Moslem community and for all the next generations. Its design features cover the following : Its construction was based on “Takwa” (devotion) to Allah. Simply, it means it was constructed by using local technology and local building material. There is clarity of function and objective in the plan, and its activities for ibadah (religious) and muamallah (social) function. But after the Prophet Mohammed passed away (633 A.D.), Mosques have been developed in a conventional manner not in accord whit what was exemplified by the prophet when he constructed the Quba mosque any more. Therefore, in designing a mosque, it should incorporate the Main basis Philosophy which is in accordance with Qur’an and Hadits. The most important is the construction of mosque should be based on “Takwa” (devotion) to Allah only.